Flavonoids: A Review On Extraction, Identification, Quantification, and Antioxidant Activity - Doloking, Haeria; Tahar, Nurshalati; Mukhriani; Surya Ningsi (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2022)
Flavonoids are polyphenolic compounds with a fifteen carbon basic skeleton (C6-C3-C6) composed of two benzene rings, A and B, connected by a pyran-C heterocyclic ring. The high interest in flavonoid research appears due to the numerous benefits of this compound based on its antioxidant activity. Various authors reported multiple studies in this regard. The research on methods of extraction, identification, quantification, and testing of antioxidant activity is compiled in this review. The most important part of this study is a review of the antioxidant activity assay method, which is equipped with the reaction mechanism.